The effects of plyometric training on sprint performance and repeated sprint ability of futsal players - Bennadja, M.; Benrabah, K.; Fayal, K. M.; el Amine, O. A. (The Russian Journal of Physical Education and Sport, 2018)
The aim of this study was to verify the efficiency of plyometric training in improving sprint performance and the repeated sprint ability (RSA) of futsal players. Methods.Twenty amateur futsal players (age 20.25± 1.8 years, body mass 75.3 ± 8.4 kg, height 174.8 ± 4.37 cm and body mass index23.1 ± 1.8 kg·m-2), the futsal players from Tissemsilt University league division. For the purposes of the protocol, we divided the group into an experimental group (EG) and a control group (CG) of 10 players respectively were thus created, at the beginning of the experimental protocol there was no significant difference between the two groups. The preliminary tests required subjects to perform a Sprint test, a Repeated sprint ability test (RSA), a counter movement jump (CMJ) and squat jumps (SJ). Results.The experimental group (EG), took place over a period of 8 weeks with an increasing and progressive increase of the workload, had two training sessions per week at a rate of 1h30 per session. The plyometric training (PT) consisted of 2—7 sets of 10 repetitions with120-second rests. On completion of the intervention, post-tests were conducted. The results showed significant increases in the CMJ, RSA and Sprint test on sand and compared with control group (p < 0.05). Conclusions.The results show that a protocol such as the one proposed here improves the physical quality of the ability to repeat sprints (p <0.001), while remaining in a type of work relatively close to the solicitations generated by futsal. Indeed, plyometry is a method involving the stretch-and-relax cycle of the muscle, most often during bouncing, as the players can use them during matches. In addition, our protocol also improved the maximup running speed on a repetition (p <0.05) and the maximum jump height with pre-movement (p <0.05). These two physical qualities may allow players to take advantage more often over their direct opponents.